A precise asteroseismic age and metallicity for HD 139614: a pre-main-sequence star with a protoplanetary disc in Upper Centaurus–Lupus. Issue 2 (20th January 2021) - Murphy, Simon J; Joyce, Meridith; Bedding, Timothy R; White, Timothy R; Kama, Mihkel
ABSTRACT: HD 139614 is known to be a ∼14-Myr-old, possibly pre-main-sequence star in the Sco-Cen OB association in the Upper Centaurus-Lupus subgroup, with a slightly warped circumstellar disc containing ring structures hinting at one or more planets. The star's chemical abundance pattern is metal-deficient except for volatile elements, which places it in the λ Boo class and suggests it has recently accreted gas-rich but dust-poor material. We identify seven dipole and four radial pulsation modes among its δ Sct pulsations using the TESS light curve and an échelle diagram. Precision modelling with the mesa stellar evolution and gyre stellar oscillation programs confirms it is on the pre-main sequence. Asteroseismic, grid-based modelling suggests an age of 10.75 ± 0.77 Myr, a mass of 1.52 ± 0.02 M ⊙, and a global metal abundance of Z = 0.0100 ± 0.0010. This represents the first asteroseismic determination of the bulk metallicity of a λ Boo star. The precise age and metallicity offer a benchmark for age estimates in Upper Centaurus–Lupus, and for understanding disc retention and planet formation around intermediate-mass stars.